2004
DOI: 10.1088/0022-3727/37/3/016
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-voltaic characteristics of Au–porous silicon interfaces

Abstract: The humidity-voltaic effect, i.e. generation of open-circuit voltage (Voc), in Au–porous silicon (PS) interface in humid atmosphere (up to 450 mV at 95% relative humidity) in dark and daylight illumination is discovered. The humidity-stimulated voltage generation is attributed to the splitting of water and hydrogen molecules on the surfaces of the Au catalyst, where further diffusion penetration of hydrogen ions into the Au–PS interface results in the formation of dipoles, thus inducing Voc across dipoles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…But the discovery of room-temperature photo-and electroluminescence by L. Canham in 1990 boosted the research on porous silicon because of the huge potential in silicon-based integrated sensing and photonic devices (Canham, 1990(Canham, , 1997b(Canham, , 1997c(Canham, ,1997dCanham et al,1991). Also there is a number of publications with the physical and chemical properties, and different applications of PS such as solar cells (Menna, 1997;Aroutiounian , 2004) integrated light-emitting devices on silicon chips (Bondarenko et al, 1997a(Bondarenko et al, , 1997bNakajima et al 2004), selective chemical, gas and humidity sensors (Sailor, 1997), pressure sensors (Pramanik et al, 2005), bio-sensors based on functionalized PS substrates (Dzhafarov et al 2004;DeLouise, 2004), electrolyte-insulator-semiconductor capacitor (EISCAP) based on silicon and PS for detecting different organic materials. Another important characteristic of PS is the ability to tailor the material morphology for the desired applications.…”
Section: Applications Of Porous Siliconmentioning
confidence: 99%
“…But the discovery of room-temperature photo-and electroluminescence by L. Canham in 1990 boosted the research on porous silicon because of the huge potential in silicon-based integrated sensing and photonic devices (Canham, 1990(Canham, , 1997b(Canham, , 1997c(Canham, ,1997dCanham et al,1991). Also there is a number of publications with the physical and chemical properties, and different applications of PS such as solar cells (Menna, 1997;Aroutiounian , 2004) integrated light-emitting devices on silicon chips (Bondarenko et al, 1997a(Bondarenko et al, , 1997bNakajima et al 2004), selective chemical, gas and humidity sensors (Sailor, 1997), pressure sensors (Pramanik et al, 2005), bio-sensors based on functionalized PS substrates (Dzhafarov et al 2004;DeLouise, 2004), electrolyte-insulator-semiconductor capacitor (EISCAP) based on silicon and PS for detecting different organic materials. Another important characteristic of PS is the ability to tailor the material morphology for the desired applications.…”
Section: Applications Of Porous Siliconmentioning
confidence: 99%
“…It is shown that NaBO 2 byproduct of reaction (20) can be recycle back to NaBH 4 using coke or membrane (Kojima & Haga, 2003). The effect, similar to humidity-voltaic effect (Dzhafarov et al, 2004), i.e. the generation a voltage between the contacts to Au film and Si under humidity exposition, was also discovered on dipping of Au/PS/Si structure into NaBH 4 solution .…”
Section: Wwwintechopencommentioning
confidence: 84%
“…The Au/PS/Si structures were fabricated by the evaporation of a thin Au film onto the PS surface with a porosity of 65% at room temperature by using the electronbeam technique (Dzhafarov et al, 2004). The thickness of the deposited Au film was 150 nm, as obtained by measurements during the evaporation using a deposition controller (Inficon, Leybold).…”
Section: Wwwintechopencommentioning
confidence: 99%
See 2 more Smart Citations